STRATEGI PEDAGOGI KREATIF DALAM MENGHADAPI ZERO ATTENTION SPAN PADA SISWA PENGGUNA TIKTOK DAN REELS: KAJIAN LITERATUR TERHADAP PENDEKATAN PEMBELAJARAN ERA DIGITAL - Itsna Rusydiana Itsna (STAI Ma'had Aly Al-Hikam Malang, 2025)
The rapid evolution of digital technologies has significantly influenced the way students engage with information, particularly with the widespread use of short video applications such as TikTok and Instagram Reels. These platforms, while offering entertainment and easily digestible content, also contribute to the phenomenon of